Empowering Deaf Students Through Entrepreneurship Workshop with A Community Service Initiative by Telkom University - Arifputri, Aiza Nabilla; Gracia, Amanda Bunga; Seprina, Wa Ode; Ekaputri, Sarah Derma; Putri, Nandita Alya (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2025)
This article discusses a community service project conducted by Communication Science and Public Relations lecturers from the Faculty of Communication and Social Sciences at Telkom University in collaboration with Cicendo State Special School in Bandung. The project aims to empower hearing- impaired students by providing vocational and entrepreneurship training, addressing broader challenges faced by people with disabilities in Indonesia. Empowerment is conducted through training that includes three sessions. The first session is a presentation on entrepreneurship theory, the second session involves practical application of the Business Model Canvas, and the third session is a group activity to encourage teamwork and creativity. The results show a significant improvement in students' understanding of business concepts and their ability to develop viable business models. Challenges related to varying literacy levels among students were addressed by providing additional support and resources. This initiative highlights the importance of inclusive education and the need for ongoing efforts to promote disability inclusion in line with Sustainable Development Goals 4 (quality education) and 10 (reduced inequalities). This Community Service Program not only equips students with practical skills but also boosts their confidence and readiness to meet industry needs.